Enhancing IT Governance Based on Risk and Security Analysis in a Private School: A COBIT 2019 Approach - Setyadi, Resad; Abdul Rahman, Aedah (Society of Visual Informatics, 2025)
Information Technology (IT) has now become an inevitable necessity for every organization, both private and non-profit Schools. IT integration directly contributes to achieving Sustainable Development Goal (SDG) 4. By effectively utilizing IT, schools can improve the quality of learning, operational efficiency, and accessibility to education. However, private schools, particularly in the Bekasi area, have not researched IT Governance (ITG) to analyze the alignment between IT strategy and business strategy. This alignment is crucial to ensuring that the investments made in procuring IT systems in schools support the goals of quality education. This research aims to identify IT governance in private schools. COBIT 2019 is used as an approach and reference for both qualitative and quantitative analysis. The study, based on initial observations, focuses on the Risk and Security domains as the main areas of concern. The analysis results indicate that several schools in Bekasi have a capability level of APO12 and APO13 at level 2, which means that IT management processes have been carried out, but are not yet optimal and have not been quantitatively measured. The recommendations highlight the need for better risk management to drive improvement. System security must be managed through adequate security controls and by enhancing human resources in the IT field via routine training. With these measures, good IT governance can support SDG 4 by creating a safe, effective, and quality education environment. These recommendations are expected to serve as a reference for several private schools in Bekasi, enabling them to achieve higher educational standards.